International Nautical Periphery Observing, For National Retreat - R.Giri,; K. Thirupura sundari, (International Journal of Psychosocial Rehabilitation, 2020)
Though there are so many means and agreements between the adjacent countries in sharing the maritime boundary, the issues in connection with the sharing of water and hence the related resources have not come to an end. As a perfunctory measure the issues between India and SriLanka in sharing the Sea border has been dealt in herewith. The major diplomatic problem between India and Sri Lanka is the shooting of fishermen on the pretext of trespassing international waters. This mission demonstrates a novel technique to identify international sea boundary with the use of GPS enabled boats along with protective measures for proper usage of boats. Any intrusion within hundred meters of the international nautical waters will be promptly determined and an appropriate alert signal will be given. Further movement in the direction will lead to cut off of fuel supply. Apart from this an anti-smuggling mechanism is integrated into the boat using RFID tags. This module also incorporates temperature and humidity sensors for weather monitoring. This plan will be a pioneer effort in making the countries sharing the maritime border to have a harmonious and peaceful relationship by saving the precious human lives. Now a days as countries face number of threats and terrorists intrusion spoiling the good wealth and the sanity of the sea sharing countries this will give a clear idea to dodge such inhumane activities by the disruptive evils